How do physicians estimate cardiovascular risk in the el-derly using E-health - a pilot study - Sorina Maria Aurelian; Justin Aurelian; Simona Isabelle Stoica; Andreea Iulia Vlădulescu-Trandafir; Andreea Zamfirescu; Gelu Onose (Balneo and PRM Research Journal)
Cardiovascular pathology encompasses a wide range of diseases characterized by common risk factors such as atherosclerotic disease, diabetes, and arterial hypertension. These conditions can be effectively mitigated through the adoption of a healthy lifestyle. Additionally, telemedicine, along with other forms of direct or indirect electronic interaction, may play a significant role in the prevention of cardiovascular diseases.In order to evaluate the perception of doctors and elderly patients from Bucharest county, as cardiovascular risk and the preventive role of telemedicine means, we created a specific questionnaire. We collected by a online questionnaire: demographic data, level of education, medical software applications used, cardiovascular parameters, telemedicine com-pliance. The obtained data were processed using Windows Office program. The surveyed doctors performed telemedicine using WhatsApp (in 55% of cases), phone short message text (in 40% of cases). and platform ASSMB (0.5%). Doctors' preferences in telemedicine were to asses the cardiovascular pathology (75%), cognitive disorders (65%), and functional (60%) evaluations. The majority of 50% of patients will resort to alternative consultations (through physical examination and telemedicine) in the future only if it is strictly necessary. Doctors and patients were predominantly women, with the majority residing in the urban environment. Telemedicine was carried out using WhatsApp for doctors and patients. Most doctors believe that telemedicine will improve the doctor-patient relationship and therapeutic compliance and monitoring and consultations will take place at the office and via telemedicine. The majority of patients will resort to alternative consultations methods (physical examination/ telemedicine) in the future when deemed necessary; a significant number of the patients would encompassing both in-person visits and telemedicine options